Methods and Materials for Religious Development in Increasing Religiosity in the Elderly at PSLU Tresna Werdha, South Lampung (Jurnal Bimbingan dan Konseling Islam, 2022)
This study discusses the methods and materials of religious development in increasing religiosity in the elderly at Tresna Werdha Natar UPTD, South Lampung. This research is a qualitative research with analytical descriptive method. Data was collected through interviews, observation and documentation. The results of this study indicate that the method used in religious development, (1) Lectures (Khitobah) is delivered using polite, gentle and gentle language and language that is easily understood by the elderly and words that contain safety. (2) demonstrations or direct practice of practical methods are carried out so that the elderly quickly understand and can do the readings or movements that are taught. (3) Discussion (Mujadalah) is the implementation of presenting the material through the submission of problems whose solutions are carried out together. while the material provided when religious guidance for the elderly is aqidah which is related to faith in Allah SWT. Sharia material that discusses the rules created by Allah or the main ones created in dealing with God, with Muslim brothers, with fellow human beings, with nature and its relationship with life. There are three forms of morals taught at the Tresna Werdha Home, namely morals to Allah, and morality to the Prophet, morality to humans, and morals to other creatures.